PENGARUH MOTIVASI, KOMITMEN KARYAWAN, DAN STRES KERJA TERHADAP PRESTASI KERJA KARYAWAN BAGIAN PRODUKSI DI SALAH SATU PERUSAHAAN SEMEN DI JAWA TENGAH - Meisya Rizki Damaranti; Ming Ming Lukiarti (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2024)
The purpose of this study is to demonstrate and elucidate the impact of employee commitment and motivation. The impact of work-related stress on the productivity of production staff at a Central Java cement company. The employed research methodology is quantitative in nature, placing emphasis on the analysis of numerical data (numbers) through the application of statistical methods. The sampling method employs cluster random sampling with a probability sampling component. Through the distribution of questionnaires, gather data, which will subsequently be analyzed using SPSS software. The data utilized in this study comprises subject data, which is collected from respondents via questionnaires that were disseminated. In order to ascertain the impact of the dependent variable, work performance, on the independent variables of motivation, employee commitment, and work stress, multiple linear regression was applied to the data. A total of 100 people were included in the research sample. Workers in the production department of a cement firm in Central Java were found to be significantly more productive when they were motivated and committed to their job. On the flip side, there is a positive correlation between work stress and the performance of production department employees at the same organization, although this correlation is not statistically significant.